Differentiated muscle cells of salamander Pleurodeles waltl re-enter the cell cycle. - Cai, Hao; Hua, Yao; Wang, Shihao; Wang, Heng (Histochemistry & Cell Biology, 2025)
Salamander Pleurodeles waltl is an emerging animal model for developmental and regenerative biology studies. However, the exploration of skeletal muscle regeneration has been hindered by the absence of suitable in vitro cell systems for in-depth mechanism research. In this study, we established a protocol for the cultivation of muscle stem cells derived from Pleurodeles waltl for cell biology experiments. Trunk and limb muscles were minced and digested with collagenase. Cells with a high nucleoplasmic ratio were isolated from the muscle tissue. Immunofluorescence and RT-PCR analysis revealed that these proliferating cells expressed the typical muscle stem cell markers. Furthermore, these cells demonstrated effective myogenic differentiation in vitro, as evidenced by the expression of the myogenic differentiation marker protein, myosin heavy chain. Additionally, it was observed that cultured myotubes derived from these cells initiated DNA synthesis and upregulate cell cycle genes upon stimulation with a high concentration of serum. Notably, the muscle stem cells (Pw-1) maintained a steady proliferation rate even after undergoing 35 subcultures. In conclusion, this study has successfully established a method for isolating and cultivating muscle stem cells from salamanders, confirming the dedifferentiation potential of the myotubes derived from these cells. This methodology provides a valuable tool for exploring the molecular mechanisms that govern skeletal muscle regeneration.